(untitled) (Orfeu, 2021)
The book Challenges in Music Education was launched via videoconference in December 2020. It consists of seven chapters written by nine researchers, most of them from English-speaking countries. The texts were translated into Portuguese. The challenges of music education, from the appropriation of principles of music psychology field, are present in most chapters. The main themes are: teacher education in music; childhood music education by generalist teachers; benefits of music in the child’s integral education; young musicians in the mobile technology generation; improvisation, creativity and social processes; practice of research in music.